PENGARUH PERSEPSI DUKUNGAN SOSIAL TERHADAP SUBJECTIVE WELL-BEING PADA GURU HONORER SEKOLAH DASAR NEGERI DI JAKARTA UTARA - Mauna Mauna; Puspa Irmandari Kurnia (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2018)
This reasearch was conducted to find out the effect of perceived social support toward subjective well-being on elementary honorary teachers in North Jakarta. Incidental sampling was used as technique sampling with 135 elementary honorary teachers as sample. Multidimensional Scale Perceived Social Support (MSPSS) was used to measure perceived social support, meanwhile the subjective well-being measured by Satisfaction With Life Scale (SWLS) and Scale of Positive and Negative Experience (SPANE). The result show that perceived social support gives significant influence toward subjective well-being, which is 5,4%. As the influenced or result is positive, it means higher perceived social support higher subjective well-being on elementary honorary teachers in North Jakarta and vice verca